USE OF CLUSTERS AND MIND MAPS IN TEACHING THE RUSSIAN LANGUAGE (World Bulletin of Education and Learning, 2025)
The article discusses innovative methods for visualizing educational information - clusters and mental maps (mind maps) - and analyzes the possibilities of their use in Russian language lessons. It is proven that these techniques contribute to the development of critical and associative thinking, systematization of knowledge and increased motivation of students.
Keywords: Cluster, mental map, mind map, Russian language, visualization, systematization, associative thinking.